Hemichorea associated with polycythaemia vera - MİDİ, İPEK (SPRINGER, 2006)
Chorea is a rare complication of polycythaemia vera. Polycythaemic chorea occurs predominantly in females and usually in generalised form. We present a 66-year-old woman with acute onset hemichorea-ballism with no vascular pathology in the basal ganglia region. A clear relationship was observed between the onset of chorea and worsening of haematological parameters in the patient. After repeated phlebotomies the patient's clinical status was improved. Polycythaemic chorea must be considered, especially in the elderly, as early diagnosis leads to effective treatment and prevention of complications.
Keywords: chorea; polycythaemia vera; elderly; movement disorder; CHOREA